Gender inequality: issues, challenges and new perspectives: Ed. by Feyza Bhatti & Elham Taheri, 2024, London, United Kingdom, IntechOpen, 300 pp., £114 Hardcover, ISBN:978-1-83769-020-6. - Hua, Jing; Zhao, Tianyue (Gender, Place & Culture: A Journal of Feminist Geography, 2025)
The main focus of "Gender Inequality: Issues, Challenges and New Perspectives" is to explore the multifaceted nature of gender inequalities across various global contexts. The book, edited by Feyza Bhatti and Elham Taheri, compiles academic contributions that address disparities in education, employment, health, and political representation, emphasizing the ongoing challenges faced by women and marginalized genders, particularly in low- and middle-income countries. It examines the intersections of gender with other identity categories and advocates for nuanced, collaborative approaches to promote equity and sustainable change. The volume aligns with the United Nations Sustainable Development Goals, particularly SDG 5, which aims to achieve gender equality and empower all women and girls.